Analisis Tingkat Kesukaan dan Daya Simpan Asinan Rumput Laut (Gracillaria sp.) - Wulandari, Sri; Harianti, Harianti; Andi Lawi, Yeni Savitri; Suprianto, Suprianto; Ningsih, Nining Adia (Jurnal Riset Diwa Bahari (JRDB), 2024)
Pickled Gracillaria sp. is a seaweed-based pickle. Seaweed is one of the seafood commodities that has many uses, economic value, and has a complete nutritional content. Pickled Gracillaria sp. is a form of processed diversification from seaweed, so this study aims to analyze the level of liking based on organoleptic tests, and the shelf life of processed Gracillaria sp. pickles. The processing of Gracillaria sp. into pickles and analysis of shelf life testing was carried out at the CV. LARS Production House. The research method used is quantitative descriptive method, while data analysis uses ANOVA. The results of the research on the level of favorability test based on the organoleptic test showed that the level of liking based on organoleptic tests is at 200C for texture, aroma, and taste. However, the color was preferred in the processed Gracilaria sp. at 300C. It can be seen that the majority of panelists dislike the texture, aroma, color and taste at 400C. While testing the shelf life of the anova test results showed that there was no real effect and influence on the shelf life testing of pickled products.